3D hierarchical porous structure formed by CS/GP/Ni0.5Co0.5Fe2O4 for high-efficiency microwave absorption. (January 2023) - Sun, Jin; Chen, Juan; Ge, Heyi; Yang, Yuxuan; Wang, Haisheng; Li, Nuo; Sun, Hao
Highlights: Corn stalk/grapefruit peel/Ni0.5 Co0.5 Fe2 O4 composites were prepared. The RLmin reaches −43.95 dB and the EAB is 4.81 GHz. The 3D hierarchically porous structure not only improve the conductive loss and multiple polarization intensity, but also benefit the impedance matching. Abstract: Preparation of light and efficient microwave absorbing materials is considered as a good solution to electromagnetic wave pollution. It is expected to achieve high-performance absorbing materials by combining light carbon-based materials with high reflection loss (RL) ferrite materials. Herein, corn stalk (CS)/ grapefruit peel (GP)/Ni0.5 Co0.5 Fe2 O4 composites were prepared by a simple solvothermal method. By adjusting the ratio of CS/GP, a 3D hierarchically porous structure composed of 0D Ni0.5 Co0.5 Fe2 O4, 1D CS and 2D GP was gained. This unique structure can effectively improve the conductive loss and multiple polarization intensity. Meanwhile, it contributes to the dielectric-magnetic combination, which leads to impedance matching. The minimum reflection loss reaches −43.95 dB and the corresponding effective absorption bandwidth is up to 4.81 GHz with 3 mm thickness. It provides a valuable way to realize light and efficient electromagnetic wave absorption.